Can the variance in DP World Tour golfers' drive distance be predicted from kinetic variables during a countermovement jump and isometric mid-thigh pull? - Bage, T.; Bishop, C.; Coughlan, D.; Wells, J. (The Journal of Strength and Conditioning Research, 2025)
In recent years, a growing body of research has investigated the relationships clubhead velocity has with kinetic variables during a countermovement jump (CMJ) and isometric mid-thigh pull (IMTP). However, to date, no research has investigated the relationships these kinetic variables have with real-world drive distance (DD) in elite DP World Tour golfers. The purpose of this investigation was to assess if CMJ positive impulse (PI), CMJ net impulse (NI), IMTP peak force (PF), force at 200 milliseconds, force at 250 milliseconds, and force at 300 milliseconds could predict the variance in elite DP World Tour golfers DD during a real-world tournament season. Twenty-five DP World Tour golfers performed CMJs and IMTPs on force plates in a real-world setting, with DD assessed using DP World Tour statistics. Hierarchical multiple regression analysis was used to assess if kinetic variables significantly predicted the variance in DP World Tour Golfers' DD. Statistical significance for this investigation was set at p = 0.05 with effect size determined using the f2 statistic. The results of the investigation note that model 2 (CMJ PI and CMJ NI) was the best fit, significantly predicting (R2 = 0.279, p = 0.05) the variance in DP World Tour Golfers' DD, which represented a large effect size (f2 = 0.39). These findings support the use of CMJ PI and CMJ NI when physically profiling elite golfers. In addition, strength and conditioning practitioners should consider utilizing modalities aimed at increasing CMJ impulse when working with golfers.